THE EFFECT OF SALES GROWTH, OPERATIONAL EFFICIENCY AND CAPITAL STRUCTURE ON PROFITABILITY IN THE FOOD AND BEVERAGE COMPANY PT. INDOFOOD CBP SUKSES MAKMUR TBK IN 2015-2024. - Poni Yanita; Dona Elvia Desi; Tiara Lilis Surya; Nosa Indah (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
This study aims to analyze the influence of Sales Growth, Operational Efficiency, and Capital Structure on Profitability at the food and beverage company PT Indofood CBP Sukses Makmur Tbk for the period 2015–2024. The variables used in this study include Sales Growth (SG), Operational Efficiency (BOPO), Capital Structure (DER), and Profitability (ROA). The analytical method used is multiple linear regression analysis with t-tests, F-tests, and coefficient of determination (R²) using data from the company's annual financial statements. This research was conducted at PT Indofood CBP Sukses Makmur Tbk, which is listed on the Indonesia Stock Exchange, as the source of financial data. Data were obtained from the company's annual financial statements, accessed through the official Indonesia Stock Exchange website and https://www.indofoodcbp.com. The analytical tool used in this study was multiple linear regression with the help of SPSS version 29. The results showed that, partially, there was no significant effect between Sales Growth and Profitability (ROA). This is indicated by a significance value of 0.386, which is greater than 0.05 (0.386 > 0.05). Operational Efficiency partially had no significant effect on Profitability (ROA). This is indicated by a significance value of 0.695, which is greater than 0.05 (0.695 > 0.05). Capital Structure (DER) partially had a significant effect on Profitability (ROA). This is evidenced by a significance value of 0.001, which is less than 0.05 (0.001 < 0.05). Simultaneously, there was a significant effect between Sales Growth, BOPO, and DER on ROA. This is evidenced by the calculated F-value of 25.720, where the calculated F-value is greater than the F-table (25.720 > 4.76), and the significance value of 0.000, which is less than 0.05 (0.000 < 0.05). The adjusted R² value of 92.7% indicates that the variation in profitability can be explained by these three independent variables, while the remaining 7.3% is influenced by other factors outside the study.